Data Processing for Laser Beam Impact Modelling - Hájková, Jana (Computing and Informatics, 2013)
This paper summarizes the data preprocessing methods used for modelling of laser beam impact. At the beginning, it gives a short overview of physical background of interaction between a laser beam and processed material. Also the input data sets are described and the way of their acquisition is shown, so that the reader could get a good idea of the whole problem. The main content of the paper is formed by description of the data preparation process that consists of several steps -- automatic heat-affected area detection, samples parameterization and their surface approximation. In all cases our methods with the best results are described in a detail. At the end of the paper, our results are summarized, discussed and possible plans for the future research are introduced.